The Problem of Translating the Social Taboo between Ellipsis and Euphemism - Ouameur, Lamia (Journal of Human Sciences, 2022)
Our study aims at highlighting the methods adopted in the translation of the social Taboo in all its manifestations in the Algerian novel, we have divided our work into two parts: in the theoretical part, we tried to define some concepts, then we touched upon the problems that face the translator while dealing with the social Taboo, and the most adopted translational methods to render it. In the practical part, we made an analytic and descriptive study of an Algerian novel trying to answer the following question: what is the most suitable method adopted in the translation of the social Taboo in the Algerian novel: Ellipsis or Euphemism?